2017
DOI: 10.1016/j.jip.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel member of genus Iflavirus in Helicoverpa armigera

Abstract: The cotton bollworm, Helicoverpa armigera, is one of the most important agricultural pests of many economic crops worldwide. Herein, we found a novel single-strand RNA virus by RNA-Seq and Polymerase Chain Reaction (PCR) method in H. armigera named Helicoverpa armigera iflavirus (HaIV), which possessed a genome with 10,017 nucleotides in length and contained a single large open reading frame (ORF) encoding a putative polyprotein of 3,021 amino acids with a predicted molecular mass of 344.16 kDa and a theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
(62 reference statements)
4
19
0
Order By: Relevance
“…However, recent studies on an iflavirus of Helicoverpa armigera revealed the presence of up to 10 6 iflavirus genomes/μg of larval feces [47]. This was sufficient to assure the horizontal transmission of the iflavirus to conspecific larvae.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies on an iflavirus of Helicoverpa armigera revealed the presence of up to 10 6 iflavirus genomes/μg of larval feces [47]. This was sufficient to assure the horizontal transmission of the iflavirus to conspecific larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Iflavirus in cotton bollworm (HaIV, around 28%) (Yuan et al, 2017) and Drosophila Nora virus (around ##%) (Habayeb et al, 2009). In addition, the HaNV titre of sodium hypochlorite-treated eggs was significantly lower than for non-treated eggs (t = 2.840, df = 4, P = 0.047; Fig 4), suggesting that the vertical transmission is mainly due to transovum transmission (i.e.…”
Section: Hanv Transmission Strategiesmentioning
confidence: 98%
“…An N-strain (Non-infected) laboratory culture of H. armigera, uninfected with known viruses Helicoverpa armigera densovirus-2 (HaDV2), Helicoverpa armigera iflavirus (HaIV), HaNPV, HaNV and known bacterium Wolbachia, was established as described previously (Xu et al, 2014;Yuan et al, 2017;Zhou et al 1998).…”
Section: Uninfected Colony Construction and Pcr Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iflaviruses are diverse in their sequence identities and host taxa. For example, the polyprotein sequence of Helicoverpa armigera iflavirus shows a relatively higher similarity (61.0%) with the protein of the Lymantria dispar Iflavirus 1 [15]. However, the two mulberry silkworm infecting iflaviruses, Bombyx mori iflavirus and infectious flacherie virus, show only a relatively lower identity (23%) [16].…”
Section: Introductionmentioning
confidence: 99%